Impact of a Nurse-Led Work-Based Intervention on Job Performance and Job Satisfaction Among Nurses in Selected Hospitals in Erode - P. Padmavathi; T.K. Kiruthika; K. Chandramathi; C. Jayalakshmi; V. Jayalakshmi; J. Jayapriya; J. Jeevitha; R. Jeevitha; A. Kanimozhi; J. Kanmanipriya (International Journal of Evidence Based Nursing And Practices, 2026)
Job satisfaction is a critical aspect of nurses’ professional lives, influencing patient safety, staff morale, productivity, performance, and overall quality of care. Higher levels of job satisfaction have been linked to improved patient outcomes. This study aimed to assess the level of job satisfaction among staff nurses before and after a nurse-led work-based intervention, evaluate the effectiveness of the intervention, and examine the association between posttest job satisfaction scores and selected demographic variables. A pre-experimental, one-group pretest–posttest design was employed at the Government Headquarters Hospital in Erode. A total of 60 female staff nurses aged between 20 and 58 years, meeting the inclusion criteria, were selected using purposive sampling. Initially, pretest data on job satisfaction were collected. Following this, participants were introduced to a nurse-led work-based intervention, which involved bedside handovers and structured briefing sessions. Nurses practiced these procedures for one week, after which posttest data were collected. The pretest mean score was 215.701 (99.41%), indicating an ambivalent level of job satisfaction. After the intervention, the posttest mean score increased to 300.05 (138.87%), reflecting a satisfactory level of job satisfaction, with a mean difference of 125.112%. The paired t-value was 19.1159, which is substantially higher than the table value of 3.460, demonstrating the intervention’s statistical significance. Furthermore, significant associations were observed between job satisfaction and demographic variables such as marital status and type of family. Overall, the findings indicate that the nurse-led work-based intervention was highly effective in improving job satisfaction among staff nurses, highlighting the importance of structured, practice-oriented strategies in enhancing workplace satisfaction and overall performance.
Keywords: Job satisfaction; nurse-led intervention; pretest–posttest design; staff nurses; work-based practices